The Effect of Processing and Rheological Variables on the Morphology of Dermal Electrospun Scaffold (Journal of Fiber Bioengineering and Informatics, 2018)
The human skin is the largest organ which protects the body from disease and physical damage. When the skin has been seriously damaged through disease or burns, the body cannot act fast enough to produce necessary replacement cells. Artificial skin grafts were developed as a way to prevent such consequences. This work is related to the design of advanced dermal scaffolds (non-woven fibrous mats) to provide multifunctional properties. Defined target properties are attained by distributing specified base materials at multiple length scales ranging from several nanometers to millimeters. Tissue scaffolds were developed using the electrospinning process, which creates a non-woven fibrous construction of high permeability and proper mechanical integrity similar to the scale of the extra-cellular matrix of cells.
Keywords: Elecrospun processing; dermal scaffold; structural optimization; rheological parameters